Evaluasi CIPP Dalam Penerapan Aplikasi Disdukcapil Banjarbaru Online Pada Kelurahan Guntung Paikat - Rabbiah Damayanti Lestari; Taufik Arbain (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2026)
This research is motivated by service disruptions within the Disdukcapil Banjarbaru Online application, specifically regarding account verification failures and the absence of notifications for completed applications. This study aims to analyze and evaluate the service workflow of the application in Guntung Paikat Village, ranging from the initial application submission to the completion of population administration services. Furthermore, it identifies inhibiting factors such as human resources, facilities and infrastructure, the application system, and community participation. This study employs a qualitative approach utilizing the CIPP (Context, Input, Process, Product) evaluation model. The results indicate that in the context aspect, limited socialization persists, preventing the application’s goal of facilitating public access to population services from being fully realized. In the input aspect, findings reveal limited human resource readiness, a lack of technical assistance from the Banjarbaru Department of Population and Civil Registration (Disdukcapil) to the village level, and the absence of formal complaint mechanisms and coordination channels. In the process aspect, workflow obstacles were identified, including account verification failures, missing completion notifications, and system malfunctions such as lag or “force closes” during document uploads. Finally, in the product aspect, the application’s rating on the Google Play Store declined from 3.3 to 2.9 within one year, indicating a decrease in user satisfaction. These findings suggest that the implementation of the Disdukcapil Banjarbaru Online application in Guntung Paikat Village has not yet operated optimally.